Pulsatile insulin release from pancreatic islets with nonoscillatory elevation of cytoplasmic Ca2+. - Westerlund, J (1997)
The relationship between insulin release and cytoplasmic Ca2+ concentration ([Ca2+]i) was studied in isolated pancreatic islets from ob/ob mice. Although [Ca2+]i was low and stable in the presence of 3 mM glucose, basal insulin release exhibited low amplitude pulsatility, with a frequency of 0.32 +/- 0.04 min-1. Depolarization by raising K+ from 5.9 to 30.9 mM or by the addition of 1 mM tolbutamide caused a pronounced initial insulin pulse followed by declining pulses, but there was no change in frequency. This decline in amplitude of the insulin pulses was prevented in similar experiments performed in the presence of 11 mM glucose. Corresponding measurements of [Ca2+]i in islets exposed to tolbutamide or the high K+ concentration revealed stable elevations without oscillations. Although the [Ca2+]i level is an important determinant for the rate of secretion, the results indicate that pulsatile insulin release does not always depend on [Ca2+]i oscillations. It is suggested that cyclic generation of ATP may fuel pulsatile release under conditions when [Ca2+]i remains stable.